2019
DOI: 10.1108/ijoem-05-2018-0218
|View full text |Cite
|
Sign up to set email alerts
|

The intention to use Islamic banking: an exploratory study to measure Islamic financial literacy

Abstract: Purpose Several research models have been proposed in the existing literature to understand the intention to use Islamic banking where conventional bank customers are not primarily addressed. Upon measuring the level of Islamic financial literacy (IFL) among the customers of conventional banks in the UAE, the purpose of this paper is to examine the direct and indirect effects of IFL, awareness, cost and benefit, reputation and attitude towards Islamic banking on the intention of potential customers to use Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
138
1
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 89 publications
17
138
1
22
Order By: Relevance
“…The data for this study were collected through an adoptive questionnaire on a five-point Likert scale. The items for information availability, self-attribution, illusion of control, and herding were adopted from Sabir et al (2018) , while Islamic sharia literacy items were adopted from Albaity and Rahman (2018) . The population of the study was composed of investors investing in Islamic financial products and 11 banks that were targeted for data collection, four pure Islamic, and seven conventional banks with Islamic banks.…”
Section: Methodsmentioning
confidence: 99%
“…The data for this study were collected through an adoptive questionnaire on a five-point Likert scale. The items for information availability, self-attribution, illusion of control, and herding were adopted from Sabir et al (2018) , while Islamic sharia literacy items were adopted from Albaity and Rahman (2018) . The population of the study was composed of investors investing in Islamic financial products and 11 banks that were targeted for data collection, four pure Islamic, and seven conventional banks with Islamic banks.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies included this factor in their empirical research. Albaity & Rahman (2019) concluded their research that reputation of Islamic banks as corporate image plays an important role in determining the intention of consumers to patronize an Islamic bank. Kaakeh et al (2019) further reported that image influenced directly the behaviour of customers towards Islamic banking in UAE.…”
Section: The Image Of the Bankmentioning
confidence: 99%
“…Md Husin & Ab Rahman, (2016)., Aziz et al, (2020) assert that subjective norms and attitude are positively related to the intention of choosing hahal products amongst consumers. Albaity & Rahman, (2019) expressed that attitude is instrumental in deciding client conduct or behaviour. Attitude is an elementary factor that determines the performance of a person on a specific behaviour intention (Osman et al, 2019).…”
Section: Attitudementioning
confidence: 99%